Assessment of knowledge, attitude and practice (KAP) on oral health among secondary-level students: a cross-sectional study in Kathmandu, Nepal - Nishika Aryal; Anuja Rajbhandari (BMJ Public Health)
Introduction Issues with oral health (OH) are frequently overlooked until individuals feel pain or discomfort. Highlighting OH behaviours is important in creating successful interventions. Therefore, the study aimed to assess the status of knowledge, attitude and practice (KAP) and examine the association between sociodemographic factors and KAP regarding OH among secondary-level students in Kathmandu.Methods A cross-sectional descriptive study was conducted with 395 secondary-level students from five schools using a self-administered questionnaire. The study used a Chi-square test to examine the association between sociodemographic factors and KAP towards OH. Binary logistic regression was employed to analyse the relationship between dependent and independent variables.Results The study involved participants with an average age of 14.24 years, comprising 56.7% males and 43.3% females. While most students demonstrated good OH knowledge (77.2%) and positive attitudes (91.9%), there was reluctance towards dental visit. Additionally, only 41% practised adequate OH, with issues like suboptimal brushing technique, low floss use and high consumption of chocolates. Significant associations were discovered between knowledge and age group (p=0.02) and students’ grade (p<0.001). Similarly, OH practices were significantly associated with gender (p=0.008), age group and students’ grade (both p<0.001) through Chi-square analysis. Despite having satisfactory attitudes, males and younger individuals were more likely to have lower knowledge (OR=0.714 and OR=0.684, respectively) and poorer practices (OR=0.484 and OR=0.514, respectively). Overall, regardless of adequate knowledge and attitudes, adolescents showcased unsatisfactory OH practices.Conclusions This study emphasises the significance of improving real-life OH habits and bridging the gap with targeted interventions like educational programmes, counselling and parental involvement. These efforts are crucial for turning knowledge and positive attitudes into consistent and effective oral care practices.